Relative influence of sulodexide and pentoxifylline to the skin microcirculation in the experimental streptozotocin-induced diabetic angiopathy - Chekhlova, O. V.; Rosha, L. G. (Journal of Education, Health and Sport, 2015)
Chekhlova O V, Rosha L G. Дослідження порівняльного впливу сулодексиду та пентоксифіліну на стан судин мікроциркуляторного русла шкіри за умов експериментальної стрептозотоцин-індукованої діабетичної ангіопатії = Relative influence of sulodexide and pentoxifylline to the skin microcirculation in the experimental streptozotocin-induced diabetic angiopathy. Journal of Education, Health and Sport. 2015;5(2):87-98. ISSN 2391-8306. DOI: 10.5281/zenodo.15574 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%282%29%3A87-98 https://pbn.nauka.gov.pl/works/540092 http://dx.doi.org/10.5281/zenodo.15574 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.10.2014. Revised 18.01.2015. Accepted: 25.01.2015. УДК 616.13.-002.28-031.37+557.146.1 ДОСЛІДЖЕННЯ ПОРІВНЯЛЬНОГО ВПЛИВУ СУЛОДЕКСИДУ ТА ПЕНТОКСИФІЛІНУ НА СТАН СУДИН МІКРОЦИРКУЛЯТОРНОГО РУСЛА ШКІРИ ЗА УМОВ ЕКСПЕРИМЕНТАЛЬНОЇ СТРЕПТОЗОТОЦИН-ІНДУКОВАНОЇ ДІАБЕТИЧНОЇ АНГІОПАТІЇ RELATIVE INFLUENCE OF SULODEXIDE AND PENTOXIFYLLINE TO THE SKIN MICROCIRCULATION IN THE EXPERIMENTAL STREPTOZOTOCIN-INDUCED DIABETIC ANGIOPATHY О. В. Чехлова, Л. Г. Роша O V Chekhlova, L G Rosha Одеський національний медичний університет. Odessa National Medical University Реферат Наводяться дані експериментальних досліджень, присвячених дослідженню порівняльної терапевтичної ефективності сулодексиду при лікуванні експериментальної стрептозотоцин-спричиненої діабетичної ангіопатії. В якості препарату порівняння було обрано традиційно застосований при діабетичних ураженнях судин мікроциркуляторного русла пентоксифілін. Отримані результати показують, що у щурів в умовах стрептозотоцин-спричиненої моделі цукрового діабету протягом 6 тижней перебігу патологічного стану формується діабетична ангіопатія. Лікування діабетичної ангіопатії із застосуванням сулодексиду та пентоксифіліну призводить до відновлення усіх ланок мікроциркуляторного русла. Сулодексид, на відміну від пентоксифіліну, покращує переважно прекапілярну ланку мікроциркуляторного русла. Антитромботична дія сулодексиду переважає порівняно з такою у пентоксифіліну. Лікування сулодексидом ефективніше відновлює структуру і функцію ендотелію порівняно з такими ефектами пентоксифіліну. Автори висловлюють, що отримані дані є експериментальним обгрунтуванням доцільності клінічного застосування сулодексиду при лікуванні діабетичної ангіопатії, а також його застосування з профілактичною метою у хворих на цукровий діабет. Ключові слова: цукровий діабет, діабетична ангіопатія, судини мікроциркуляторного русла, сулодексид, пентоксифілін, патогенетична терапія. Реферат Приводятся данные экспериментальных исследований, посвященных исследованию сравнительной терапевтической эффективности сулодексида при лечении экспериментальной стрептозотоцин–вызванной диабетической ангиопатии. В качестве препарата сравнения был выбран традиционно использующийся при диабетических поражениях сосудов микроциркуляторного русла пентоксифиллин. Полученные результаты показывают, что у крыс в условиях стрептозотоцин-индуцированной модели сахарного диабета в течение 6 недель течения патологического состояния формируется диабетическая ангиопатия. Лечение диабетической ангиопатии с применением сулодексида и пентоксифиллина приводит к восстановлению всех звеньев микроциркуляторного русла. Сулодексид, в отличие от пентоксифиллина, улучшает преимущественно прекапиллярное звено микроциркуляторного русла. Антитромботическое действие сулодексида преобладает по сравнению с таковым у пентоксифиллина. Лечение сулодексидом эффективнее восстанавливает структуру и функцию эндотелия по сравнению с таковыми эффектами пентоксифиллина. Авторы делают вывод о том, что полученные данные являются экспериментальным обоснованием целесообразности клинического применения сулодексида при лечении диабетической ангиопатии, а также его применения с профилактической целью у больных сахарным диабетом. Ключевые слова: сахарный диабет, диабетическая ангиопатия, сосуды микроциркуляторного русла, сулодексид, пентоксифиллин, патогенетическая терапия. Abstract The data of the experimental trials are given devoted to the sulodexide comparative therapeutic efficacy investigation in conditions of experimental streptozotocine-induced diabetic angiopathy. Pentoxifylline widely used in cases of microcirculatory vessels diabetic damages was chosen as the comparative drug. The data obtained showed the possibility pf diabetic angiopathy development in streptozotocine-treated diabetic rats 6 weeks from the beginning of the trials. Sulodexide and pentoxifylline were effective in diabetic angiopathy treatment that resulted in microcirculatory vessels all links restoration. Sulodexide, unlike pentoxifylline, improves mainly precapillary link of the microcirculatory vessels. Sulodexide antithrombotic efficacy prevails the same in pentoxifylline. Sulodexide treatment resulted in the more effective endothelial structure and function restoration compare with pentoxifylline. The authors conclude that the data obtained are the experimental background of sulodexide clinical efficacy testing reasonability in diabetic angiopathy treatment as well in case of its prophylactic use in diabetic patients. Key words: diabetus mellitus, diabetic angiopathy, microcirculatory vessels, sulodexide, pentoxifylline, pathogenetic therapy.